The Rise of the Digital Creative Economy: Caribbean Challenges and Opportunities - Nurse, Keith (Editorial Uniagustiniana, 2018)
The burgeoning creative economy is making an in-creased contribution to gdp, exports and employment across the global economy. Although this is increas-ingly so in the developing world, from a trade stand-point, most developing countries operate at the low val-ue-added end of the value chain, resulting in large trade imbalances in creative goods, services and intellectual property. As such, to tap into present and emerging op-portunities, especially in the context of the rise of the digital creative economy, developing countries are en-couraged to not only improve the quality and market-ability of existing creative content they must also find ways to participate in the higher value-added segments such as online distribution is also highlighted. Drawing on the experience of the Caribbean, the paper presents a roadmap for value chain integration via mechanisms focused on trade support programmes that target in-dustrial upgrading and enterprise development.